Kharsutra Ligation with Partial Fistulectomy-As a Treatment for Anterior Trans-Sphincteric Fistula in Ano- A Case Study - Patel, Soham; Thumar, Neha; Sharma, Rajesh; Shah, Harshit (Asian Journal of Pharmaceutical Research and Development, 2019)
Perianal fistulas are prevalent in 0.01- 0.05% of the population and are commonly associated with discomfort and morbidity to the patient. Surgical treatment is the only modality of management of fistulas with the pitfall of high rate of recurrence In Transsphincteric fistulas, the track passes from the inter sphincteric space through the external sphincter into the Perianal region. Surgical treatment of perianal fistulas frequently affects fecal continence. Sphincter saving techniques like Ksharsutra (cutting seton) and fistulectomy has been advocated to minimize the risk of sphincter injury.